Application of long-term athlete development model in Hungarian speed skating - Telegdi, A.; Trzaskoma-Bicsérdy, G.; Bognár, J. (Journal of Human Sport & Exercise, 2025)
The Long-Term Athlete Development (LTAD) model has been applied in the areas of theory of training, methodology, and nurture-education in Hungarian speed skating. The goal of our research was to analyse whether the official documents of the Hungarian National Skating Federation contain detailed guidelines on how to use LTAD and to explore the deficiencies when put into practice. We conducted document analysis (N = 5) and semi-structured interviews (N = 15) with coaches, athletes and parents. Both analyses were based on the following three factors: 1) long-term planning and goals, 2) application of LTAD, 3) multi-sided communication. We can state that official documents of the Skating Federation do contain proper guidelines on how to use LTAD. The results of interviews show that coaches have sufficient knowledge to effectively transmit LTAD methods and have actively done so with the athletes they are coaching. The same cannot be stated in regard to informing parents of LTAD. This is despite the fact that it is beneficial for the athletes to get support and confirmation from their parents in addition to their coaches.